2020
DOI: 10.2196/18043
|View full text |Cite
|
Sign up to set email alerts
|

Association of Social Media Use and High-Risk Behaviors in Adolescents: Cross-Sectional Study

Abstract: Background Previous studies have demonstrated the prevalence of social media use and identified the presence of high-risk behaviors among adolescents, including self-harm and sharing of sexually explicit messages. Objective This study aimed to identify patterns in the amount of time spent on social media by adolescents who engage in high-risk behavior and the extent to which they use social media as a platform for sharing such behaviors. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Vente et al . (2020) reiterated these findings in their study, reporting increased levels of nonsuicidal self‐injury in adolescents who had excessive use of multiple social media platforms, including Instagram. This conflicting evidence, with some suggesting that Instagram is the most influential platform in regard to DSH, and others suggesting it is multiple platforms was an important finding from the literature and highlights the need for further research into these claims.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Vente et al . (2020) reiterated these findings in their study, reporting increased levels of nonsuicidal self‐injury in adolescents who had excessive use of multiple social media platforms, including Instagram. This conflicting evidence, with some suggesting that Instagram is the most influential platform in regard to DSH, and others suggesting it is multiple platforms was an important finding from the literature and highlights the need for further research into these claims.…”
Section: Resultsmentioning
confidence: 85%
“…Vente et al . (2020) reiterated this, finding that for the participants in their study, many used Instagram as a tool to self‐report and communicate with others regarding their DSH. However, concerns were raised by Nesi et al .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies identified that social media use can also have harmful effects on adolescents such as cyberbullying, sexting, sending embarrassing photos, publicly sharing location, and the sharing of dangerous pranks and games [ 21 , 22 , 23 , 24 , 25 ]. In a recent study, social media revealed to be a means by which adolescents self-reported sharing thoughts and actions of self-harm with others [ 26 ]. Therefore, several social media platforms have started to limit the sharing of explicit pictures or messages of self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…Although risk factors and causes are multifactorial, the influence of popular culture on society and adolescents in this media-driven generation cannot be mitigated. In fact, recent cross-sectional studies and meta-analyses have demonstrated a relationship between increased social media use and high-risk behavior among adolescents and the development of depressive symptoms [ 3 , 4 ]. Although the impact of social media and its effect on shaping self-identity in adolescents have been observed [ 5 ], the impact of music has not been studied.…”
Section: Introductionmentioning
confidence: 99%